2015
DOI: 10.1016/j.epsl.2015.06.056
|View full text |Cite
|
Sign up to set email alerts
|

Melting of the primitive martian mantle at 0.5–2.2 GPa and the origin of basalts and alkaline rocks on Mars

Abstract: We have performed piston-cylinder experiments on a primitive martian mantle composition between 0.5 and 2.2 GPa and 1160 to 1550 • C. The composition of melts and residual minerals constrain the possible melting processes on Mars at 50 to 200 km depth under nominally anhydrous conditions. Silicate melts produced by low degrees of melting (<10 wt.%) were analyzed in layers of vitreous carbon spheres or in micro-cracks inside the graphite capsule. The total range of melt fractions investigated extends from 5 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
109
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(120 citation statements)
references
References 68 publications
8
109
3
Order By: Relevance
“…Olivines in primitive depleted shergottites reach Mg# of 0.86 (Usui et al, 2008), which requires extensive (>50%) melting of the Martian primitive mantle if the BSM has Mg# = 0.75, which is unlikely to be achieved when shergottites formed (Musselwhite et al, 2006). On the other hand, with an Fe-poor Martian primitive mantle (Mg# ∼ 0.80), much lower degrees of mantle melting can produce the high-Mg olivine (Musselwhite et al, 2006;Collinet et al, 2015;McCoy et al, 2016). Collinet et al (2015) concluded that the Martian mantle has heterogeneous Mg# ranging between 0.75-0.82.…”
Section: Major Elements (Mg Si Fe)mentioning
confidence: 99%
“…Olivines in primitive depleted shergottites reach Mg# of 0.86 (Usui et al, 2008), which requires extensive (>50%) melting of the Martian primitive mantle if the BSM has Mg# = 0.75, which is unlikely to be achieved when shergottites formed (Musselwhite et al, 2006). On the other hand, with an Fe-poor Martian primitive mantle (Mg# ∼ 0.80), much lower degrees of mantle melting can produce the high-Mg olivine (Musselwhite et al, 2006;Collinet et al, 2015;McCoy et al, 2016). Collinet et al (2015) concluded that the Martian mantle has heterogeneous Mg# ranging between 0.75-0.82.…”
Section: Major Elements (Mg Si Fe)mentioning
confidence: 99%
“…Experiments performed from the wholerock composition of NWA 1068 (Filiberto et al, 2010) have identified a multiple saturation point (MSP) where olivine and orthopyroxene appear on the liquidus of NWA 1068 at 1.7 GPa and 1520°C. Under those conditions, the primitive martian mantle is expected to contain only olivine and orthopyroxene (Collinet et al, 2015). The CaO/Al 2 O 3 of NWA 1068 is super-chondritic and rules out that the parental melt derives from the primitive martian mantle by equilibrium melting.…”
Section: Parental Melt Of Nwa 1068 and Implications For The Origin Ofmentioning
confidence: 99%
“…10). The olivine compositions in equilibrium with primary martian mantle melts vary from Fo 76 for melting of the primitive martian mantle (Collinet et al, 2015) to Fo 85 for the mantle source of the depleted shergottites (Musselwhite et al, 2006). The parental melt of NWA 1068 could have been in equilibrium with Fo 80±1 olivines and would represent a primary melt of a mantle source with an intermediate Mg#.…”
Section: Parental Melt Of Nwa 1068 and Implications For The Origin Ofmentioning
confidence: 99%
“…Therefore, they have suggested a lower Fe/Mg ratio for the source of shergottites in comparison with Dreibus and Wänke (1985). Collinet et al (2015) demonstrated that the parental melt of Adirondack-class basalts of Gusev crater may be produced by ∼25 wt% partial melting of the mantle at 1.5 GPa using Dreibus and Wänke (1985) composition. Despite admitted sources of uncertainties and unknowns, the model of Dreibus and Wänke (1985) still serves as a reference model until today.…”
Section: Interior Composition From Martian Meteorites and Cosmochemicmentioning
confidence: 99%
“…It also suggests an iron-rich mantle, with differences regarding the Mg/Si ratio that has consequences on the mantle mineralogy. The validity of the geochemical models was also addressed from laboratory experiments to determine if the elements abundances of martian basalts can be formed through the magmatic differentiation of parent magma derived from mantle partial melting at high pressure (Agee and Draper 2004;Collinet et al 2015). For instance, Agee and Draper (2004) have shown that it is possible to reproduce the super-chondritic CaO/Al 2 O 3 ratio of martian basalts from partial melting at ∼5 GPa, but find it difficult to match their FeO content.…”
Section: Interior Composition From Martian Meteorites and Cosmochemicmentioning
confidence: 99%